As convenções processuais na tutela coletiva - Botelho, Ingrid Pantoja Pereira (2021)
The study aims to analyze the institute of procedural agreements through the compatibility of the Brazilian micro-system of Collective Proceedings with the Civil Procedure Code of 2015. Although this is not a novelty inserted by the 2015 Civil Procedure Code, they innovated by bringing in article 190 the general clause of negotiation, since it conceived greater autonomy to the parties, before or during the conduct of the process regarding burdens, powers, faculty and procedural duties, as well as the possibility of changes in the procedure to adjust it to the specifics of the cause. These are laws that raise new debates for civil procedure, especially when they put into question that these excessive discussions about procedural rules end up weakening the protection of the material right and ignoring the main function of procedural law: instrumentality. And it is exactly based on this premise that this paper will analyze the new proposals provided in article 190 of CPC/15 for flexibility and adaptability of the procedure, aiming at social pacification and greater efficiency through the privatization of procedural rules. The concept of the institute, its limits and applicability were analyzed, as well as its advantages and the sensitive points that guide the theme. Based on the insertion of procedural agreements in the Civil Procedure Code, we tried to demonstrate that although the CPC/15 has a proposal to protect individual trademark rights and is not concerned with the regulation of procedures aimed at collective protection, the need for research that would verticalize the question regarding the possibility of procedural agreements in the context of transindividual trademark rights would be justified. In view of this, the second chapter notes that the current legal scenario increasingly seeks to enforce the rights of the collectivity, and that the collective right goes beyond individual interests and is found in an intermediate range between private law and public law, called transindividual rights. To this end, the problems concerning the limits of the procedural convention when it comes to collective protection of rights and the possibility of relativizing such rights in order to provide greater procedural operability were evaluated. Finally, it was in this context that the subject of the study was inserted, the procedural conventions protecting rights with a social dimension of higher reach, which concern the preservation of living conditions in society, the maintenance of the state organization, and democracy.